Impact of a health coaching intervention on anthropometric indicators, physical activity, and life style of infertile women with polycystic ovary syndrome: A quasi-experimental study - Maryam Abdollahzade Delavar; Mouloud Agajani Delavar; Reza Ghadimi; Sedighe Esmaeilzadeh; Mania Amiri (BMC Research Notes)
Abstract Background The first step in managing PCOS entails lifestyle adjustments. This study explores health coaching’s impact on anthropometric measures, physical activity, and lifestyle in infertile PCOS women. Methods A quasi-experimental study included 78 infertile, overweight/obese PCOS women (aged 18–35), randomly assigned to coaching or routine care. Coaching involved six sessions (30–45 min) with a midwife coach. Primary outcome: weight change. Secondary outcomes: waist/hip circumference, waist-to-hip ratio, physical activity (IPAQ), and lifestyle (LSQ). The secondary outcomes were the waist circumference, hip circumference, waist-to-hip ratio, physical activity “based on the International Physical Activity Questionnaire (IPAQ], and lifestyle (based on the Lifestyle Questionnaire (LSQ]”. Results After the intervention, weight changes were 4.6 kg and 3.6 kg in coaching and control groups, respectively. No significant difference was observed in weight change from baseline to four months post-intervention. A significant mean difference was found between the two groups regarding changes in the waist circumference (-2.13; 95% CI, -0.22 to -4.05; P = 0.020), total physical activity (3025.22; 95% CI, 1088.68 to 4961.77; P = 0.003), and total LSQ score (11.03; 95% CI, 3.34 to 18.72; P = 0.006). Conclusion The study highlights health coaching’s benefits in reducing waist circumference, increasing physical activity, and improving lifestyle in PCOS women undergoing fertility treatments.